Some Bodies Organs Functional Status in Serious Forms of Covid-19 Disease - Umurov B.F.; Umurov Bobirjon Fayzilloyevich (Research Journal of Trauma and Disability Studies, 2024)
Changes occurring in the liver can be observed with direct exposure to the virus, systemic post-inflammatory cytokines attack (cytokines storm), hypoxia, hypovolemia in shock, hepatotoxicity of drugs. The body produces interleukins (IL-1b, IL-6, IL10) and chemokines that affect normally functioning hepatocytes. Viruses have been scientifically proven to affect the ACE2 and TMPRSS2 receptors in patients with Covid-19, but in-depth studies show that if liver protectors are not taken during treatment and when the body's immune status is not controlled, liver cells are deeply affected as a result of this disease.